Student Periodicals under Dictatorship. Notes for a Comparative Study between Spain and Argentina - Seia, Guadalupe A. (CIAN-Revista de Historia de las Universidades, 2020)
This article seeks to contribute to comparative analysis of the student periodicals under dictatorship in Spain (1939-1975) and Argentina (1976-1983). Based on a case study about the student movement at the Universidad de Buenos Aires (University of Buenos Aires), we describe the editorial experiences of students in both countries. We develop comparative keys focusing on the modalities in which the student periodicals initiated and the process by they changed their positions towards the regime. Also, we explore the relationship between the student press and the student movement of each country.
Keywords: student periodicals; university; dictatorship; Spain; Argentina